Nebeneinander - Gegenüber. (Köln : Kunsthaus Rhenania, 1989)
Stowasser, Helmut ; Lempert, Jochen ; Last, Rüdiger ; Fuchs, Gudrun ; Pick, Peter ; Fritz, Urs ; Suhr, Bernhard ; Riechers, Achim ; Spanninga, Willem ; Falley, Nicola ; Bernardy, Michael ; Brunner, Johann
Nebeneinander - Gegenüber, Kunsthaus Rhenania, Köln ; Rhenaniahalle, 19. Mai - 25. Juni 1989
boek